2020
DOI: 10.3390/su12051837
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dissonance in Sustainability Scientists Regarding Air Travel for Academic Purposes: A Qualitative Study

Abstract: The purpose of this study is to investigate in depth the perspectives of sustainability scientists regarding academic air travel, with an emphasis on cognitive dissonance and associated coping and rationalisation strategies. The research design is case study-based, focusing on a sustainability-focused academic unit in Germany. Thematic content analysis was applied to the transcripts of 11 interviews with sustainability scientists. Analytic codes were informed by prior previously identified cognitive dissonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Overwhelmed by negative information, people can feel paralyzed and start ignoring certain information (Haltinner and Sarathchandra 2018). This observation goes in line with the notion of cognitive dissonance where individuals may rationalize, underplay, or distort information to suit their personal interests and reduce the psychological discomfort resulting from holding contradictory beliefs or desires (e.g., choosing climate action vs. comfort or pleasure) (Schrems and Upham 2020). While learning about the seriousness of climate change and the mitigation potential of household actions may be insufficient to change decisions, a lack of knowledge can also (paradoxically) lead to ineffective actions (Attari et al 2010).…”
Section: Discussionsupporting
confidence: 58%
“…Overwhelmed by negative information, people can feel paralyzed and start ignoring certain information (Haltinner and Sarathchandra 2018). This observation goes in line with the notion of cognitive dissonance where individuals may rationalize, underplay, or distort information to suit their personal interests and reduce the psychological discomfort resulting from holding contradictory beliefs or desires (e.g., choosing climate action vs. comfort or pleasure) (Schrems and Upham 2020). While learning about the seriousness of climate change and the mitigation potential of household actions may be insufficient to change decisions, a lack of knowledge can also (paradoxically) lead to ineffective actions (Attari et al 2010).…”
Section: Discussionsupporting
confidence: 58%
“…Glover et al (2017) note that 'it is difficult to envision' universities reducing air travel without resisting internationalization, and it is essential that strategies attend to the systemic connections between individual academic flights and the sector-wide internationalization agenda. Reconfigured expectations that allow for virtual and remote participation, and value local forms of scholarship and impact need to proliferate throughout competitive processes (Le Quéré et al, 2015, Schrems andUpham, 2020), and drive investment into modes of research and teaching that reduce the need for physical co-presence (Glover et al, 2019.…”
Section: Action To Reduce Air Travel In Uk Universitiesmentioning
confidence: 99%
“…Ackers (2008) finds expectations of aeromobility inhibit the inclusion of foreign academics on restricted visas, disabled academics and those with care commitments that prevent long-distance travel. The view that air travel is necessary in an academic career is also not universal Font, 2020, Schrems andUpham, 2020), and the link between academic mobility and career can impact negatively on those who reject this culture, or are less able to participate (Ackers 2008). Consequently, failing to disrupt the model of aeromobility ensures an unsustainable and inequitable future for HE (Glover et al, 2019), so there is need for far greater attention to equality and inclusivity in university's decarbonization plans.…”
Section: Action To Reduce Air Travel In Uk Universitiesmentioning
confidence: 99%
“…In the EB literature, cognitive dissonance has been explored in various contexts, including climate change, water conservation, sustainable tourism, and sustainable consumption (Dolnicar, Knezevic Cvelbar, & Grün, 2017;Gadeikienė, Dovalienė, Grase, & Banytė, 2019;Taylor, Lamm, & Lundy, 2017). In a recent study, the authors reported certain levels of cognitive dissonance amongst sustainability scientists and their flight behaviors (Schrems & Upham, 2020). The authors noted that, although participants were aware of the negative impacts their flying behaviors had on the environment, they continued to engage in that same behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%